Strategic decisions and weak signals : anticipation for decision-making - Lesca, Humbert; Lesca, Nicolas (London : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2014)
An increasing number of business executives, managers and political leaders are using the concept of "weak signals" nowadays. There are also an increasing number of people trying to find out exactly what this concept means, as well as when and how to use it. Such questions arise particularly when it comes down to making strategic decisions. To help with these questions, this book defines the concept of the "weak signal" and then demonstrates how it would be useful in relation to strategic decisions, and more precisely in relation to three moments of the strategic decision, i.e.:<br.
The Subject within the Field of Management Science: Concepts and Issues / Humbert Lesca, Nicolas Lesca -- State of the Art: Systems Suggested by Previous Authors / Humbert Lesca, Nicolas Lesca -- Proposed Systems: Results of Information System Prototyping Research Conducted at the CNRS-CERAG Lab (France) / Humbert Lesca, Nicolas Lesca -- Conclusion -- Glossary.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed June 6, 2014).
Print version record.
English.
John Wiley and Sons
Keywords: Decision making -- Data processing; x; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Decision making -- Data processing